2013
DOI: 10.3390/ijerph10083296
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Food Safety Needs of Restaurants in Owerri, Imo State, Nigeria

Abstract: One hundred and forty five head chefs and catering managers of restaurants in Owerri, Nigeria were surveyed to establish their knowledge of food safety hazards and control measures. Face-to-face interviews were conducted and data collected on their knowledge of risk perception, food handling practices, temperature control, foodborne pathogens, and personal hygiene. Ninety-two percent reported that they clean and sanitize food equipment and contact surfaces while 37% engaged in cross-contamination practices. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 8 publications
1
39
0
Order By: Relevance
“…None of the food handlers 100% (n=25) had attended any specific training for food handling. In several studies, food service workers that received training had better hygiene scores and safe food handling practices than those that did not receive training [11,17,41,42]. This reveals that periodic trainings for the food handlers in this study will be of great importance towards safe food handling.…”
Section: Characteristics Of Study Respondents From Old and New Hostelmentioning
confidence: 84%
See 2 more Smart Citations
“…None of the food handlers 100% (n=25) had attended any specific training for food handling. In several studies, food service workers that received training had better hygiene scores and safe food handling practices than those that did not receive training [11,17,41,42]. This reveals that periodic trainings for the food handlers in this study will be of great importance towards safe food handling.…”
Section: Characteristics Of Study Respondents From Old and New Hostelmentioning
confidence: 84%
“…Sixteen (n=16) 64% of the individual respondents in this study did not have any formal education. Higher levels of education have been associated with better food safety knowledge awareness, and better sanitary conditions in other studies [18,42], and a study of the environmental hygiene of food service outlets were significantly associated with the age and educational level of operators [43]. A study in India indicated that food handling practices was related with educational status of food handlers [44].…”
Section: Characteristics Of Study Respondents From Old and New Hostelmentioning
confidence: 99%
See 1 more Smart Citation
“…). The WHO also reported that more than 200,000 people die annually of food poisoning in Nigeria (Onyeneho and Hedberg ). Although, the full extent of the burden and cost of unsafe food is unknown, the impact on global health, trade, and development is considered to be immense.…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization (WHO) reported that 1.8 million people died in 2005 from diseases largely due to pathogens that contaminated food and water supplies (Sudershan et al 2014 ). The WHO also reported that more than 200,000 people die annually of food poisoning in Nigeria (Onyeneho and Hedberg 2013 ). Although, the Listeria monocytogenes is a small gram-positive, oxidase-negative, nonsporulating motile bacterium.…”
Section: Introductionmentioning
confidence: 99%